Challenges Encountered and Coping Mechanism in New Learning Modality Among BSEd Students of Altavas College - Driatzen L. Javier; Kristine Joy T. Victoriano; Mikko Jan D. Lopez, EdD (Web of Journals Publishing, 2023)
The primary purpose of this study was to determine the levels of challenges encountered and coping mechanism in new learning modality among BSED students of Altavas College. The researchers collected the data by using an electronic web-based questionnaire through the Google survey tool (Google Forms) using questions modified from challenges encountered and coping mechanism. The survey comprised 2 subsections according to the participant's challenges encountered and a question corresponding to each respondent's coping mechanism. The analysis was perceived using the frequency count, percentage, and mean. Descriptive analyses were done. The result showed that the level of challenges encountered by the respondents was “evident”." This signifies that the respondents are facing more challenges in their new learning modality during the Covid-19 pandemic. Also, the level of coping mechanism of Bachelor in Secondary Education of Altavas College was described as "evident." It implies their good learning habits towards using social media and asking help from the teachers and their classmates.
Keywords: Challenges encountered, Coping mechanism, New learning modality.